2018
DOI: 10.1038/s41598-018-26305-8
|View full text |Cite
|
Sign up to set email alerts
|

On-wafer fabrication of cavity mirrors for InGaN-based laser diode grown on Si

Abstract: Direct bandgap III-V semiconductor lasers grown on silicon (Si) are highly desired for monolithic integration with Si photonics. Fabrication of semiconductor lasers with a Fabry–Pérot cavity usually includes facet cleavage, however, that is not compatible with on-chip photonic integration. Etching as an alternative approach holds a great advantage in preparing cavity mirrors with no need of breaking wafer into bars. However, gallium nitride (GaN) sidewalls prepared by dry etching often have a large roughness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…The sidewall was near 90 • steep and the surface was smoother after TMAH wet treatment. This is due to the sidewall being etched preferentially in anisotropic wet etching solution [43][44][45].…”
Section: Resultsmentioning
confidence: 99%
“…The sidewall was near 90 • steep and the surface was smoother after TMAH wet treatment. This is due to the sidewall being etched preferentially in anisotropic wet etching solution [43][44][45].…”
Section: Resultsmentioning
confidence: 99%
“…Without the aid of UV light irradiation or bias voltage, the wet etching only selectively occurs at semi-polar and non-polar planes of GaN, which would not prohibit the hydroxide ions from accessing the Ga atom [22,23,24]. It was also reported that the wet etching rate of GaN is dependent on the crystallographic planes of GaN [25,26,27]. Thus, the anisotropic wet etching of GaN generally leads to peculiar textures at different surfaces, such as trigonal prisms and hexagonal pyramids, by exposing specific crystallographic planes [21,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In the mass-production of LEDs, the LED chips are commonly cut into cuboid geometry by laser scribing without considering the sidewall orientation, which means that the exposed crystallographic planes are indecisive. Some researchers have reported that the surface morphologies are varied at different sidewalls for the striped GaN pattern and cuboid geometry LED chips after wet etching [20,25,27]. However, it is unknown whether the sidewall orientation has influence on the optical and electrical performance of LEDs with chemical etching treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical results are presented in Supplementary Figure S2. The change in the morphology of the cavity facets and slot sidewalls caused by the TMAH etching originated from the anisotropic electrochemical properties of various crystallographic planes, which has been observed and explained in our previous work [44]. During the TMAH wet etching, Ga atoms in the m-plane surface with positively charged dangling bonds attract and react with OH − in the TMAH solution, producing GaO x , which dissolves in the solution.…”
Section: Resultsmentioning
confidence: 68%